Comparative Analysis of the Human Proteome Profile in Visceral Adipose and Liver Tissue in Individuals with Obesity with and Without MASLD and MASH - Julie S. Pedersen; Lili Niu; Nicolai J. Wewer Albrechtsen; Viggo B. Kristiansen; Inge Marie Poulsen; Reza R. Serizawa; Torben Hansen; Lise Lotte Gluud; Sten Madsbad; Flemming Bendtsen (Livers)
Background/Objectives: Visceral adipose tissue (VAT) may play a direct role in the development of metabolic dysfunction-associated steatotic liver disease (MASLD) and its progression to metabolic dysfunction-associated steatohepatitis (MASH). In this study, we employed untargeted proteomics analyses on paired biopsies from VAT and liver tissues of patients with obesity, MASLD, and MASH. Our objective was to investigate tissue-specific protein expression patterns in search of a potential proteomic signature associated with MASH in both VAT and liver tissue. Methods: VAT and liver tissue were collected from 70 subjects with severe obesity (SWOs) and nine control study subjects without obesity (CON). SWOs were stratified on the basis of liver histology into LS− (no liver steatosis), LS+ (liver steatosis), and MASH. Peptides were extracted from frozen tissue and were analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). Raw files were analyzed with Spectronaut, proteins were searched against the human FASTA Uniprot database, and the significantly expressed proteins in the two tissues were analyzed. The p-values were false discovery rate (FDR) corrected. Results: A total of 59 VAT and 42 liver proteins were significantly differentially expressed between the four groups: LS−, LS+, MASH, and CON. The majority were upregulated, and many were related to lipid metabolism. In VAT, only one protein, the mitochondrial sulfide:quinone oxidoreductase (SQOR), was significantly downregulated in the MASH group only. In liver tissue from patients with MASH, six proteins were significantly altered compared with the three other groups. Correlation analyses between the top 10 positive VAT and liver proteins were dominated by inflammatory and detoxification proteins. Conclusions: The presence of MASH was not reflected in the VAT proteome, and both the VAT and the liver proteome were generally affected more by the presence of obesity than by MASLD severity. Several immunomodulating proteins correlated significantly between VAT and liver tissue and could reflect common pathophysiological characteristics.